A porous bifunctional catalyst for CO2 cycloaddition reaction and its preparation method and application
The Zn-Salen two-dimensional cationic porous covalent organic framework catalyst solves the problems of low efficiency and difficult catalyst separation in the reaction of CO2 with epoxides to form cyclic carbonates. It realizes easy separation and efficient recycling of catalyst and product, and is suitable for industrial application of CO2 cycloaddition reaction.
Patent Information
- Application Number
- CN202410663688.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-27
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-05-27
AI Technical Summary
Existing catalysts are difficult to efficiently catalyze the reaction of CO2 with epoxides to form cyclic carbonates, and the separation of catalysts from products is difficult, which affects the recycling of catalysts.
Two-dimensional cationic porous covalent organic frameworks (COFs) of Zn-Salen are used as porous bifunctional catalysts. Two-dimensional cationic COFs are formed by reacting quaternary ammonium salt intermediates with o-phenylenediamine and zinc chloride. Combined with the ion exchange preparation process, cationic metal polymers linked by covalent bonds are formed. The epoxide compound is activated by the Lewis base active center of Zn-Salen, and cyclic carbonates are generated by ring opening with nucleophiles.
It achieves easy separation of catalyst and product, improves catalytic efficiency and cycle performance, promotes the efficient reaction of CO2 with epoxides, and is suitable for large-scale industrial production.
Smart Images

Figure CN118638285B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of multifunctional catalytic preparation, and specifically relates to a porous bifunctional catalyst for CO2 cycloaddition reaction and a preparation method and application thereof. Background Art
[0002] CO2 contains carbon and is another important resource after coal, oil and natural gas. It can be used as a chemical raw material. CO2 can be reduced as a raw material to produce bulk chemical products such as CO, methanol, methane and dimethyl ether, and can also be used to produce fine chemical products such as carbonates, carbonates, carboxylic acids and their derivatives. The reduction of CO2 to produce chemical products such as CO and methanol is an "oxygen loss" conversion pathway and a high-energy consumption process. The production of carbonates and carbonates from CO2 without reduction is an "oxygen retention" conversion pathway, which not only has 100% atomic economy, but also has low energy consumption in the conversion process. It is an important way to utilize CO2 in a green and efficient resource manner.
[0003] The reaction of CO2 with epoxy compounds can produce cyclic carbonates or polycarbonates. Cyclic carbonates can be used as green high-boiling polar solvents, electrolytes for lithium-ion batteries, monomers for the synthesis of polycarbonates and polyurethanes, and important intermediates for medicines and many other fine chemicals. CO2 is an inert molecule with low energy, while epoxy compounds have large ring strains and are a class of compounds with high energy. Therefore, the reaction of CO2 with epoxy compounds to produce cyclic carbonates or polycarbonates is a thermodynamically favorable reaction. However, like other CO2 conversion pathways, this type of reaction has a high energy barrier and requires the use of a catalyst to reduce the activation energy of the reaction. Metal complexes are currently one of the catalysts used to react CO2 with epoxy compounds to produce cyclic carbonates or polycarbonates.
[0004] Metal complex catalysts have some unique advantages, including easy activation, easy structure regulation, and the ability to obtain pure chiral catalytic centers. However, metal complexes can only activate epoxides, and cannot be used alone as catalysts to catalyze the reaction of CO2 and epoxides to form cyclic carbonates. It is also necessary to add compounds with nucleophilic properties, such as tetrabutylammonium bromide, as co-catalysts to promote the ring opening of the activated epoxides. Generally, the cyclic carbonates generated by the cycloaddition of CO2 and epoxides are a type of high-boiling polar solvents. Metal complex catalysts and co-catalysts are easily dissolved in cyclic carbonates, which makes product separation and catalyst recovery difficult. Therefore, there is an urgent need to develop a bifunctional polymer catalyst that can simultaneously activate epoxides and promote their ring opening, which can easily separate the product and catalyst after the efficient catalysis of the cycloaddition reaction of CO2 and epoxides, and promote catalyst recycling. Summary of the invention
[0005] The purpose of the present invention is to provide a porous bifunctional polymer catalyst for CO2 cycloaddition reaction and a preparation method and application thereof. The method is easy to obtain the target product, has low cost and high yield, and the prepared porous bifunctional catalyst can be used in the preparation of cyclic carbonates by CO2 cycloaddition.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] A porous bifunctional catalyst for CO2 cycloaddition reaction, wherein the porous bifunctional catalyst is a two-dimensional cationic porous covalent organic framework, namely, Zn-Salen two-dimensional cationic COFs, and its chemical structure is shown in Formula III:
[0008]
[0009] Where R is H or t Bu, X is Cl, Br or I.
[0010] To achieve the purpose of the invention, the present invention also provides a method for preparing a porous bifunctional catalyst for CO2 cycloaddition reaction, comprising the following steps:
[0011] (1) Synthesis of quaternary ammonium salt intermediate: chloromethylated salicylaldehyde compound and 1,3,5-tri(pyridin-4-yl)benzene are heated to reflux in acetonitrile for 45-50 hours; after the reaction is completed, the reaction mixture is cooled to room temperature, the yellow precipitate is collected by filtration, and the precipitate is washed alternately with acetonitrile and ether for several times, and vacuum dried to obtain the quaternary ammonium salt intermediate, which is dried and sealed for storage; the molar ratio of the chloromethylated salicylaldehyde compound to 1,3,5-tri(pyridin-4-yl)benzene is (3.5-4.5):1; the ratio of the volume of acetonitrile to the molar amount of the chloromethylated salicylaldehyde compound is (6-7) mL:1 mmol;
[0012] The structural formula of the chloromethylated salicylaldehyde compound is shown in Formula I:
[0013] Where R is H or t Bu;
[0014] The structural formula of the quaternary ammonium salt intermediate is shown in Formula II:
[0015] Where R is H or t Bu;
[0016] (2) Synthesis of two-dimensional cationic porous covalent organic frameworks:
[0017] (2-1) slowly adding a 0.076 mol / L methanol solution of o-phenylenediamine to a 0.025 mol / L methanol solution containing a quaternary ammonium salt intermediate, and stirring at room temperature for 10-14 h to obtain a reaction mixture; the molar ratio of o-phenylenediamine to the quaternary ammonium salt intermediate is 1.5:1;
[0018] (2-2) zinc chloride is ultrasonically dispersed in methanol to obtain a 0.076 mol / L zinc chloride solution; the molar ratio of zinc chloride to o-phenylenediamine is 1:1;
[0019] (2-3) Add zinc chloride solution dropwise to the reaction mixture prepared in step (2-1), and a large amount of yellow precipitate appears immediately; then add DMF, continue stirring at room temperature for 5-7 hours, transfer it to a hydrothermal reactor and react at 120-125° C. for 45-50 hours, filter the collected precipitate and extract it with methanol for 22-25 hours, and vacuum dry the remaining solid product to obtain a two-dimensional cationic porous covalent organic framework [Zn-Salen(H)-COF] n+ (Cl - ) n or [Zn-Salen( t Bu)-COF] n+ (Cl - ) n ;
[0020] (3) [Zn-Salen(H)-COF] n+ (Cl - ) n or [Zn-Salen( t Bu)-COF] n+ (Cl - ) n Place in a saturated KBr or KI aqueous solution and stir thoroughly for 8-12 hours, then centrifuge to separate the solid powder, wash the ion exchange product with deionized water for 3-5 times, and place in an oven to dry to obtain a two-dimensional cationic porous covalent organic framework [Zn-Salen(H)-COF] n+ (Br - ) n or [Zn-Salen(H)-COF] n+ (I - ) n or [Zn-Salen( t Bu)-COF] n+ (Br - ) n or [Zn-Salen( t Bu)-COF] n+ (I - ) n .
[0021] Furthermore, in step (1), when R is H, the chloromethylated salicylaldehyde compound is 5-chloromethyl-2-hydroxybenzaldehyde, and its preparation process is: at room temperature, paraformaldehyde (CHO) n and 2-hydroxybenzaldehyde are added to concentrated hydrochloric acid in a mass ratio of 1:(2.5-3), the mass ratio of concentrated hydrochloric acid to 2-hydroxybenzaldehyde is (2.5-3.0):1, and the paraformaldehyde is completely dissolved by stirring; phosphorus oxychloride is slowly added dropwise to the above reaction mixture using a constant pressure dropping funnel, the mass ratio of phosphorus oxychloride to 2-hydroxybenzaldehyde is 1:(2.8-3.0), and after the dropwise addition is completed, the reaction mixture is vigorously stirred at room temperature for 22-25 hours, and white solid is precipitated during the reaction process; after the reaction is completed, deionized water is added to the reaction mixture, the volume ratio of deionized water to concentrated hydrochloric acid is (1.5-2.0:1), and the solid product is collected by filtration to obtain 5-chloromethyl-2-hydroxybenzaldehyde.
[0022] Further, the solid product is collected by filtration and washed with a 3% by mass sodium bicarbonate solution and deionized water in sequence until neutral, and then vacuum dried at 55-65° C. for 10-14 h to obtain a crude 5-chloromethyl-2-hydroxybenzaldehyde product; the obtained crude product is recrystallized from petroleum ether 2 to 3 times to obtain pure 5-chloromethyl-2-hydroxybenzaldehyde.
[0023] Furthermore, in step (1), when R is t When Bu, the chloromethylated salicylaldehyde compound is 3-tert-butyl-5-chloromethyl-2-hydroxybenzaldehyde, and the preparation process is: 3-tert-butyl-2-hydroxybenzaldehyde, paraformaldehyde and tetrabutylammonium bromide are respectively added to concentrated hydrochloric acid in a mass ratio of 3:(1-1.2):(0.4-0.5), the mass ratio between concentrated hydrochloric acid and 3-tert-butyl-2-hydroxybenzaldehyde is (1.8-2.0):1, and the reaction mixture is vigorously stirred at room temperature for 60-65h; after the reaction is completed, the reaction mixture is extracted with ether, the separated organic phase is washed with NaHCO3 solution and NaCl solution in sequence, and then dehydrated with MgSO4, and vacuum dried to obtain a yellow crystalline solid.
[0024] The specific synthetic route is as follows:
[0025]
[0026] The present invention also provides the use of the porous bifunctional catalyst in the preparation of cyclic carbonates by cycloaddition of carbon dioxide and epoxy compounds.
[0027] Furthermore, the specific process should be:
[0028] (1) adding Zn-Salen two-dimensional cationic COFs and epoxide into a reaction kettle and stirring and mixing them thoroughly; the mass ratio of Zn-Salen two-dimensional cationic COFs to epoxide is 1000:(1.5-2.5);
[0029] (2) The air in the reactor is removed by purging with CO2 3-4 times, and then the reactor is connected to a CO2 cylinder with a constant output pressure. The reactor is then heated to 60-80°C and kept warm for 15-24 hours to obtain a cyclic carbonate.
[0030] Preferably, in step (1), the epoxy compound is one of ethylene oxide, propylene oxide, epichlorohydrin, butyl ethylene oxide, styrene oxide and cyclohexene oxide.
[0031] The invention uses Zn-Salen Schiff base with high catalytic activity as Lewis base active center, firstly introduces chloromethyl group on the Salen Schiff base precursor salicylaldehyde; then reacts it with a three-pointed star organic compound containing three pyridine groups to obtain the corresponding salicylaldehyde quaternary ammonium salt compound; finally, reacts the salicylaldehyde quaternary ammonium salt compound with o-phenylenediamine and zinc salt to obtain the target compound Zn-Salen quaternary ammonium salt type two-dimensional porous cationic covalent organic framework. In addition, the counter anion Cl in the Zn-Salen quaternary ammonium salt type two-dimensional porous cationic covalent organic framework - Can be replaced by Br with stronger nucleophilicity through ion exchange - or I - In this type of Zn-Salen cationic covalent organic framework, the axial coordination site of the central Zn(II) ion of Zn-Salen is unoccupied, and it coordinates with the oxygen atom in the epoxy compound to activate it. The counter anion of the quaternary ammonium salt acts as a nucleophile to attack the activated epoxy compound to open its ring and react with CO2 to form a cyclic carbonate.
[0032] The present invention embeds the metal complex catalytic unit and the organic bridging compound into the covalent organic framework (COFs) in the form of a quaternary ammonium salt to form a cationic metal polymer organic framework connected by covalent bonds. Compared with the prior art, the present invention has the following advantages:
[0033] (1) Cationic metal polymer organic frameworks are a type of single-component bifunctional catalyst in which the metal complex can react with epoxy compounds to activate them and counteract anions (Cl - Br - ,I - ) can act as a nucleophile to open the ring of epoxy compounds;
[0034] (2) COFs, as a two-dimensional framework material, will not dissolve in the product cyclic carbonate, making it easy to separate the catalyst from the product;
[0035] (3) The Schiff base ligand in the metal-Schiff base complex is used as one of the linking units of COFs and stably fixed in the COFs structure, avoiding the problem of decreased catalytic efficiency due to the loss of catalytic units;
[0036] (4) The complex catalyst does not serve as a linking node of the polymer framework in COFs, the metal active coordination sites can be fully exposed, and the complex catalyst is evenly distributed in the COFs material, which is conducive to its contact with the reactants and ensures the catalytic reaction rate.
[0037] The above advantages are helpful to improve the catalytic efficiency and cycle performance of the catalyst, promote the metal-Schiff base complex catalyst to catalyze the reaction of CO2 and epoxy compounds to prepare cyclic carbonates, and realize large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The infrared absorption spectra of Zn-Salen two-dimensional cationic COFs and their quaternary ammonium salt precursors, (a) is [(SA-H)-TPy] 3+ Cl - 3 and [Zn-Salen(H)-COF] n+ (Cl - ) n , (b) is [(SA- t Bu)-TPy] 3+ Cl - 3 and [Zn-Salen( t Bu)-COF] n+ (Cl - ) n ;
[0039] Figure 2 It is the Zn-Salen two-dimensional cationic COFs 13 C solid state NMR spectrum, (a) for [Zn-Salen(H)-COF] n+ (Cl - ) n , (b) is [Zn-Salen( t Bu)-COF] n+ (Cl - ) n ;
[0040] Figure 3 It is the X-ray photoelectron spectrum (full spectrum) of Zn-Salen two-dimensional cationic COFs;
[0041] Figure 4 is the X-ray photoelectron spectrum of Zn-Salen two-dimensional cationic COFs, (a) C 1s, (b) N 1s, (c) Zn2p, (d) Cl 2p;
[0042] Figure 5 The X-ray diffraction patterns of Zn-Salen two-dimensional cationic COFs; (a) [Zn-Salen(H)-COF] prepared in different solvent systems n+ (Cl - ) n Powder X-ray diffraction pattern of [Zn-Salen( t Bu)-COF] n+ (Cl - ) n Powder X-ray diffraction pattern of
[0043] Figure 6 [Zn-Salen(H)-COF] n+ (Cl - ) n SEM images and EDS images of each component element; (a) is a 5um SEM image, (b) is a 2um SEM image, and (c) is an EDS image;
[0044] Figure 7 It is [Zn-Salen( t Bu)-COF] n+ (Cl - ) n SEM images and EDS images of each component element; (a) is a 5um SEM image, (b) is a 2um SEM image, and (c) is an EDS image;
[0045] Figure 8 The N2 adsorption-desorption curve and pore size distribution of Zn-Salen two-dimensional cationic COFs; (a) [Zn-Salen(H)-COF] n+ (Cl - ) n N2 adsorption-desorption curves (a) and (b) for [Zn-Salen(H)-COF] n+ (Cl - ) n The pore size distribution diagram of (c) [Zn-Salen ( t Bu)-COF] n+ (Cl - ) n The N2 adsorption-desorption curve (d) is [Zn-Salen ( t Bu)-COF] n+(Cl - ) n The pore size distribution diagram of
[0046] Fig. 9 The thermogravimetric curves of Zn-Salen two-dimensional cationic COFs; (a) is [Zn-Salen(H)-COF] n+ (Cl - ) n , (b) is [Zn-Salen( t Bu)-COF] n+ (Cl - ) n ;
[0047] Fig.10 It is [Zn-Salen( t Bu)-COF] n+ (Cl - ) n (a) obtained after ion exchange [Zn-Salen ( t Bu)-COF] n+ (Br - ) n (b) and [Zn-Salen( t Bu)-COF] n+ (I - ) n (c) X-ray energy spectrum;
[0048] Fig.11 [Zn-Salen(H)-COF] n+ (Cl - ) n The statistical diagram of the catalytic cycle performance (a) and the infrared absorption spectrum before and after the cycle (b);
[0049] Fig.12 It is [Zn-Salen( t Bu)-COF] n+ (Cl - ) n The statistical diagram of the catalytic cycle performance (a) and the infrared absorption spectrum before and after the cycle (b);
[0050] Fig.13 The mechanism diagram of the cycloaddition reaction of CO2 and epoxides catalyzed by Zn-Salen two-dimensional cationic COFs (X - represents a halogen ion). DETAILED DESCRIPTION
[0051] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0052] Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products with a purity of analytical grade or above.
[0053] 5-chloromethyl-2-hydroxybenzaldehyde (SA-H) used in the following examples is synthesized by the following synthesis steps: 3.76g of paraformaldehyde is added to a three-necked flask containing 64mL of concentrated hydrochloric acid at room temperature, stirred to completely dissolve the paraformaldehyde, and then 9.6g of 2-hydroxybenzaldehyde is added. 2.4mL of phosphorus oxychloride is slowly added dropwise to the above reaction mixture using a constant pressure dropping funnel. After the dropwise addition is completed, the reaction mixture is vigorously stirred for 24h at room temperature, and white solid is precipitated during the reaction. After the reaction is completed, 100mL of deionized water is added to the reaction mixture, and the solid product is collected by filtration and washed with a sodium bicarbonate solution and deionized water with a mass fraction of 3% in sequence until neutral, and then vacuum dried at 60°C for 12h to obtain a crude product of 5-chloromethyl-2-hydroxybenzaldehyde. The obtained crude product is recrystallized 2 to 3 times with petroleum ether to obtain 12.2g of pure 5-chloromethyl-2-hydroxybenzaldehyde, with a yield of 91%. Melting point 86.5~87.5℃. 1 HNMR(600MHz,DMSO-d6)δ11.29(s,1H),10.94(s,1H),10.28(s,1H),10.10(s,1H),7.84 (d,J=22.3Hz,2H),7.72(s,1H),7.58(s,1H),7.03(d,J=9.0Hz,1H),4.58-4.38(m,1H).
[0054] The 3-tert-butyl-5-chloromethyl-2-hydroxybenzaldehyde (SA-tBu) used in the following examples was synthesized by the following synthesis steps:
[0055] 3-tert-butyl-2-hydroxybenzaldehyde (2.70 g, 15.2 mmol), paraformaldehyde (1.00 g, 33.3 mmol) and tetrabutylammonium bromide (0.47 g, 1.5 mmol) were added to 11 mL of concentrated hydrochloric acid, and the reaction mixture was vigorously stirred at room temperature for 3 days. After the reaction was completed, the reaction mixture was extracted with ether (3 × 15 mL), and the separated organic phase was washed with NaHCO3 (5%, 2 × 10 mL) and brine (2 × 10 mL) in sequence, and then dehydrated with 1-2 g MgSO4, and dried in vacuo to obtain a yellow crystalline solid. 1HNMR(600MHz,DMSO-d6)δ11.90(t,J=2.4Hz,1H),9.98(t,J=2.3Hz,1H),7.75(q,J=3.1 ,2.5Hz,1H),7.63(q,J=3.1,2.4Hz,1H),4.81(t,J=2.4Hz,2H),1.39(t,J=2.4Hz,9H).
[0056] Example 1
[0057] A method for preparing a porous bifunctional catalyst for CO2 cycloaddition reaction comprises the following steps:
[0058] (1) Quaternary ammonium salt intermediate ([(SA-H)-TPy] 3+ Cl - 3 or [(SA- t Bu)-TPy] 3+ Cl - 3) Synthesis
[0059] A chloromethylated salicylaldehyde compound (SA-H or SA-tBu) (16.0 mmol) and 1,3,5-tri(pyridin-4-yl)benzene (1.20 g, 4.0 mmol) were heated to reflux in acetonitrile (100 mL) for 48 h. After the reaction, the reaction mixture was cooled to room temperature, the yellow precipitate was collected by filtration, and washed alternately with acetonitrile and ether several times, and vacuum dried to obtain a quaternary ammonium salt intermediate, which was dried and sealed for storage.
[0060] [(SA-H)-TPy] 3+ Cl - 3: Yield 75%. 1 H NMR (600MHz, DMSO-d6) δ11.90(t,J=2.4Hz,1H),9.98(t,J=2.3Hz,1H),7.75(q,J=3.1,2.5Hz,1H),7.63(q,J=3.1,2.4Hz,1H),4.81(t,J=2.4Hz,2H).
[0061] [(SA- t Bu)-TPy] 3+ Cl - 3: The yield is 94%. 1 H NMR(600MHz,Methanol-d4)δ9.96(s,1H),9.37–9.27(m,2H),8.69–8.62(m,2H),7. 88–7.81(m,1H),7.46(dd,J=74.4,2.3Hz,1H),5.95(s,1H),1.42(d,J=15.7Hz,9H).
[0062] (2) Two-dimensional cationic porous covalent organic framework ([Zn-Salen(H)-COF] n+ (Cl - ) n or [Zn-Salen( t Bu)-COF] n+ (Cl - ) n )
[0063] A methanol solution (5 mL) of o-phenylenediamine (0.04 g, 0.38 mmol) was slowly added to the quaternary ammonium salt intermediate ([(SA-H)-TPy] 3+ Cl - 3 or [(SA- t Bu)-TPy] 3+ Cl - 3) (0.25mmol) in methanol solution (10mL), the reaction mixture was stirred at room temperature for 12h to obtain a reaction mixture; zinc chloride (0.05g, 0.38mmol) was ultrasonically dispersed in 5mL methanol, and then added dropwise to the above reaction mixture, and a large amount of yellow precipitate appeared immediately; 10mL DMF was added to the reaction system, and after stirring at room temperature for 6h, it was transferred to a 50mL hydrothermal reactor and reacted at 120℃ for 48h; the collected precipitate was filtered and extracted with methanol for 24h, and the remaining solid product was vacuum dried to obtain a two-dimensional cationic porous covalent organic framework [Zn-Salen(H)-COF] n+ (Cl - ) n or [Zn-Salen( t Bu)-COF] n+ (Cl - ) n .
[0064] The product prepared in this example was subjected to the following series of performance characterizations, and the specific characterization results are as follows:
[0065] (1) Infrared absorption spectrum (IR) analysis of Zn-Salen two-dimensional cationic COFs
[0066] The infrared absorption test of Zn-Salen two-dimensional cationic COFs and its quaternary ammonium salt precursor was carried out. Figure 1 By comparing the infrared absorption spectra of the target product Zn-Salen two-dimensional cationic COFs and its quaternary ammonium salt precursor, it can be found that the 1633 cm -1The absorption peak of the aldehyde group C=O on the benzene ring in the quaternary ammonium salt precursor is near 1608cm -1 An absorption peak attributed to the stretching vibration of the C=N double bond appeared nearby, proving that the aldehyde group in the quaternary ammonium salt precursor condensed with o-phenylenediamine to form a Schiff base structure.
[0067] (2) Zn-Salen 2D cationic COFs 13 C solid state NMR spectroscopy analysis
[0068] use 13 C solid-state NMR was used to further characterize the chemical structure of Zn-Salen two-dimensional cationic COFs. Figure 2 As shown. The NMR peak of the carbon atoms in the Schiff base structure in Zn-Salen two-dimensional cationic COFs is around 160ppm, the broad peak in the 100-155ppm region corresponds to the NMR peaks of carbon atoms in different chemical environments on the benzene ring and pyridine ring in Salen ligand and tripyridylbenzene, and the NMR peak around 41ppm is attributed to the methylene carbon atom in the pyridine quaternary ammonium salt. In addition, [Zn-Salen( t Bu)-COF] n+ (Cl - ) n of 13 The very obvious sharp peaks at 34ppm and 28ppm in the C solid NMR spectrum correspond to the two carbon atoms on the tert-butyl group. 13 C solid-state nuclear magnetic resonance tests showed that the salicylaldehyde pyridinium quaternary ammonium salt precursor condensed with o-phenylenediamine to form the expected two-dimensional layered structure.
[0069] (3) X-ray photoelectron spectroscopy analysis of Zn-Salen two-dimensional cationic COFs
[0070] X-ray photoelectron spectroscopy (XPS) was performed on the two-dimensional Zn-Salen cationic COFs to determine the elemental composition. Figure 3 The XPS spectrum clearly shows that the two-dimensional Zn-Salen cationic COFs synthesized in Example 1 contain C, N, O, Zn 2+ and Cl - Among them, the binding energy peak near 285eV is the characteristic peak of carbon, which can be further convoluted into three peaks at 284.6, 285.5 and 286.1eV ( Figure 4 a), corresponding to the binding energies of C=C, CC and CN bonds in Zn-Salen cationic COFs; the binding energy peak near 285 eV is the characteristic peak of N element, which can be further convoluted into two peaks at 400.36 and 399.11 eV ( Figure 4 b), corresponding to pyridine N + -C and Schiff base N=C bond binding energy; Zn 2+ There are two characteristic peaks at 1044.99 and 1022.05 eV ( Figure 4 c), respectively Zn 2p 1 / 2 and Zn 2p 3 / 2 The corresponding peak, Cl - The characteristic energy spectrum peak is around 199eV, which can be convoluted into two peaks at 198.51 and 200.16eV ( Figure 4 d), corresponding to Cl2p. The above results show that Zn 2+ Coordinated with Salen to form a complex.
[0071] In addition, XPS was used to perform a semi-quantitative analysis of the elements in the two-dimensional Zn-Salen cationic COFs, and the results are shown in Table 1. The C content in the two-dimensional Zn-Salen cationic COFs is about 80%, because their structural carbon skeleton is mainly composed of carbon elements. Due to the presence of tert-butyl groups [Zn-Salen(H)-COF] n+ (Cl - ) n The carbon content in [Zn-Salen( t Bu)-COF] n+ (Cl - ) n Table 1 also gives the element content ratios of N / Zn and Zn / Cl. The results show that the ratio of N / Zn is slightly higher than the theoretical value, which may be due to the presence of guest molecules such as DMF in their pores. Theoretically, the ratio of Zn / Cl in the synthesized two-dimensional Zn-Salen cationic COFs should be 1 / 2, but the XPS semi-quantitative results show that the ratio of Zn / Cl should be 1.05, which may be because XPS can only detect the element content on the surface of the material, and Cl - As counter anions, a large portion of them are located inside COFs and are not exposed on the surface.
[0072] Table 1 XPS semi-quantitative analysis results of the contents of main elements in two-dimensional Zn-Salen cationic COFs
[0073]
[0074] a The theoretical value calculated from the structural formula of the minimum repeating unit of the polymer.
[0075] (4) Crystallinity analysis of Zn-Salen two-dimensional cationic COFs
[0076] The crystallinity of Zn-Salen two-dimensional cationic COFs was determined by powder X-ray diffraction (PXRD). n+ (Cl - ) n The PXRD pattern is as follows Figure 5 a. When methanol is used alone as the reaction solvent, the sample obtained has a weak X-ray diffraction peak, indicating that this type of cationic polymer has the possibility of forming an ordered crystalline phase. Therefore, the effect of a mixed solvent system composed of methanol and other solvents of different polarities on the crystallinity of Zn-Salen cationic COFs was explored. The results showed that only the sample obtained when methanol / DMF mixed solvent was used as the reaction solvent had a strong X-ray diffraction peak, while the samples obtained when a mixed solvent composed of methanol and non-polar solvent mesitylene (SDS) or methanol and more polar dimethyl sulfoxide (DMSO) was used as the reaction solvent had no X-ray diffraction peak. [Zn-Salen ( t Bu)-COF] n+ (Cl - ) n The sample also shows very strong X-ray diffraction peaks ( Figure 5 b) In the PXRD spectrum of the two-dimensional Zn-Salen cationic COFs, the diffraction peak appears in a larger 2θ angle range, indicating that the pore structure in this type of cationic COFs is small, which is caused by the staggered stacking of the two-dimensional Zn-Salen polymer layers.
[0077] (5) Surface morphology analysis of Zn-Salen two-dimensional cationic COFs
[0078] The surface structure and composition of Zn-Salen two-dimensional cationic COFs were characterized by scanning electron microscopy (SEM) and X-ray energy dispersive spectroscopy (EDS). Figure 6 and Figure 7 ). SEM images show that Zn-Salen two-dimensional cationic COFs aggregate into smooth spherical particles. EDS images show that the main elements C, N, Zn, and Cl are evenly distributed on the polymer surface.
[0079] (6) Pore structure analysis of Zn-Salen two-dimensional cationic COFs
[0080] The pore structure of Zn-Salen two-dimensional cationic COFs was characterized by N2 physical adsorption-desorption instrument. The adsorption-desorption isotherms were shown in Figure 2. Figure 8As shown. Based on the IUPAC classification, the adsorption curves of the synthesized two-dimensional cationic Zn-Salen COFs are all typical type-IV adsorption isotherm curves. [Zn-Salen(H)-COF] n+ (Cl - ) n The adsorption-desorption isotherm shows a separation between the adsorption and desorption lines at relatively high relative pressures, presenting an H3-type hysteresis loop ( Figure 8 a). [Zn-Salen(H)-COF] n+ (Cl - ) n has pore sizes mainly distributed in the micropore and mesopore regions ( Figure 8 b), where the pores with pore sizes between 2 and 5 nm account for the largest proportion, and the average pore size is 2.011 nm, indicating that [Zn-Salen(H)-COF] n+ (Cl - ) n layers stack in a staggered manner to form smaller mesoporous materials. [Zn-Salen( t Bu)-COF] n+ (Cl - ) n shows hysteresis loops both at low relative pressures (0.1 < P / P0 < 0.6) and at relatively high relative pressures (0.6 < P / P0 < 0.9) ( Figure 8 c). The hysteresis loop at relatively high relative pressures is the same as that of [Zn-Salen(H)-COF] n+ (Cl - ) n . Smaller mesopores are formed by the stacking of polymer layers. The hysteresis loop at low relative pressures is due to the presence of tert-butyl groups in the compound, which increases the distance between layers and generates larger slits. [Zn-Salen(H)-COF] n+ (Cl - ) n has a pore size distribution concentrated around 4 nm and 10 nm, with an average pore size of 7.865 nm, showing obvious characteristics of mesoporous materials ( Figure 8 d). The physical structure characteristic parameters obtained from pore size tests are shown in Table 2. [Zn-Salen(H)-COF] n+ (Cl - ) n and [Zn-Salen( t Bu)-COF] n+ (Cl - ) n have specific surface areas of 16.475 m 2 / g and 26.863 m 2 / g, respectively.
[0081] Table 2 Physical structure characteristic parameters of Zn-Salen two-dimensional cationic COFs
[0082]
[0083] (7) Thermal stability analysis of Zn-Salen two-dimensional cationic COFs
[0084] The thermal stability of Zn-Salen two-dimensional cationic COFs was characterized by thermogravimetric analysis. Fig. 9 As shown. [Zn-Salen(H)-COF] n+ (Cl - ) n The weight loss from room temperature to 200℃ is about 2.88%, [Zn-Salen( t Bu)-COF] n+ (Cl - ) n The weight loss at 250°C is about 2.33%. The reason for the weight loss at this stage is that the guest solvent molecules in the structural pores are removed, but the overall structure remains stable, indicating that they are stable before 200°C. The temperature of the cycloaddition reaction of epoxides and CO2 generally does not exceed 120°C, indicating that the stability of the synthesized Zn-Salen two-dimensional cationic COFs meets the requirements for being a catalyst for this reaction.
[0085] Example 2
[0086] The [Zn-Salen(H)-COF] prepared in Example 1 n+ (Cl - ) n or [Zn-Salen( t Bu)-COF] n+ (Cl - ) n ) was placed in a saturated KBr or KI aqueous solution and stirred for 8-12 hours, then the solid powder was separated by centrifugation, the ion exchange product was washed with deionized water for 3-5 times, and then dried in an oven to obtain a two-dimensional cationic porous covalent organic framework [Zn-Salen(H)-COF] n+ (Br - ) n or [Zn-Salen(H)-COF] n+ (I - ) n or [Zn-Salen( t Bu)-COF] n+ (Br - ) n or [Zn-Salen( tBu)-COF] n+ (I - ) n .
[0087] In the cycloaddition reaction of CO2 and epoxy compounds catalyzed by the Zn-Salen two-dimensional cationic bifunctional catalyst, its counter anion acts as a nucleophile to attack the activated epoxy compound to open the ring. In the Zn-Salen two-dimensional cationic polymer synthesized in Example 1, the counter anion is Cl - , whose nucleophilicity is relatively small, so the present invention uses Br with stronger nucleophilicity - and I - Replace Cl - , in order to improve the catalytic performance of the bifunctional catalyst. This embodiment selects [Zn-Salen ( t Bu)-COF] n+ (Cl - ) n , through ion exchange, the Cl - Become Br - or I - . The elemental analysis results show that [Zn-Salen( t Bu)-COF] n+ (Cl - ) n After soaking in saturated KBr or KI solution for several hours, it turned into [Zn-Salen( t Bu)-COF] n+ (Br - ) n or [Zn-Salen( t Bu)-COF] n+ (I - ) n ( Fig.10 ).
[0088] The ion-exchanged catalyst was put into the cycloaddition reaction of ECH and CO2, and the experiment was carried out under the conditions (reaction temperature 80°C, reaction pressure 0.1MPa). The experimental results are shown in Table 3. The results show that [Zn-Salen( t Bu)-COF] n+ (Br - ) n or [Zn-Salen( t Bu)-COF] n+ (I - ) n It shows better catalytic performance and can completely convert EHC into the corresponding cyclic carbonate in a shorter time: [Zn-Salen( tBu)-COF] n+ (Br - ) n As a catalyst, the complete conversion of ECH into cyclic carbonate can be achieved within 18 hours. t Bu)-COF] n+ (I - ) n When used as a catalyst, ECH can be completely converted to cyclic carbonate within 12 hours, which is much shorter than [Zn-Salen( t Bu)-COF] n+ (Cl - ) n The above results show that enhancing the nucleophilicity of the counter anion in the polymer catalyst can greatly improve the catalytic activity of the catalyst, which is consistent with the theory.
[0089] Table 3 [Zn-Salen ( t Bu)-COF] n+ (Br / I - ) n Catalytic cycloaddition reaction of ECH and CO2
[0090]
[0091] Example 3
[0092] The porous bifunctional catalyst prepared in Example 1 is used in the preparation of cyclic carbonates by cycloaddition of carbon dioxide and epoxy compounds. The application test process and results are as follows:
[0093] (1) [Zn-Salen(H)-COF] n+ (Cl - ) n Catalytic performance
[0094] First, the catalytic performance of Zn-Salen two-dimensional cationic bifunctional catalyst in the cycloaddition of CO2 and epoxides to prepare cyclic carbonates was explored at 80°C. The reaction equation is as follows. The amount of catalyst is determined according to the active sites of Zn. A catalyst amount of 0.25 mol% is selected to participate in the reaction, [Zn-Salen(H)-COF] n+ (Cl - ) n The reaction results are shown in Table 4.
[0095]
[0096] Table 4 [Zn-Salen(H)-COF] n+ (Cl - )n Catalytic cycloaddition reaction of epichlorohydrin (ECH) and CO2
[0097]
[0098]
[0099] a Reaction conditions: ECH (5 mmol), catalyst (20 mg), 80 °C.
[0100] It can be seen from Table 4 that [Zn-Salen(H)-COF] n+ (Cl - ) n At 80°C, 1.0MPa, and 20mg of catalyst, the ECH can be completely converted after 12h reaction, and the yield of cyclic carbonate is 99% (Example 4). In addition, it can be seen from Table 4 that the yield decreases with the decrease of pressure. At normal pressure (0.1Mpa), the yield of cyclic carbonate is only 56.8% (Example 6). When the reaction time is extended under normal pressure, it is found that the conversion rate of ECH increases slowly. After 24h of reaction, the yield is still only 78.5% (Example 8), and the yield can reach 97.4% after 36h of reaction (Example 10). Therefore, for [Zn-Salen(H)-COF] n+ (Cl - ) n The optimal reaction pressure is 1.0MPa and the reaction time is 12h.
[0101] Then, the cyclic performance of the catalyst was tested under the conditions of 80°C, 1.0 MPa, and reaction time of 12 h. Fig.11 Cyclic experiments show that [Zn-Salen(H)-COF] n+ (Cl - ) n It has good recyclability. [Zn-Salen(H)-COF] n+ (Cl - ) n After being recycled for 6 times, the catalytic activity did not decrease significantly, and the yield was still 96.1% and the selectivity was 99% ( Fig.11 a). FT-IR was used to characterize the recycled catalyst. The results showed that the infrared absorption spectrum of the recovered catalyst ( Fig.11 b) The spectrum is basically consistent with that of the fresh sample.
[0102] (2) [Zn-Salen( t Bu)-COF] n+ (Cl - ) nCatalytic performance
[0103] Given that [Zn-Salen(H)-COF] n+ (Cl - ) n It can catalyze the cycloaddition reaction of epoxy compounds under normal pressure, and [Zn-Salen( t Bu)-COF] n+ (Cl - ) n It has a more developed pore structure, so this example studies its catalytic performance at 80°C and 0.1MPa, and the results are shown in Table 5. As can be seen from Table 5, at normal pressure, with the extension of reaction time, the conversion rate of ECH and the selectivity of cyclic carbonate are steadily improved. After 21h of reaction, the conversion rate of ECH and the selectivity of cyclic carbonate both reach 99%, indicating that [Zn-Salen( t Bu)-COF] n+ (Cl - ) n It showed excellent catalytic efficiency under mild conditions. This may be because [Zn-Salen ( t Bu)-COF] n+ (Cl - ) n The more developed pore structure is more conducive to the enrichment of CO2 and epoxides and the outward diffusion of products.
[0104] Table 5 [Zn-Salen ( t Bu)-COF] n+ (Cl - ) n Catalytic cycloaddition reaction of ECH and CO2
[0105]
[0106] a Reaction conditions: ECH (5 mmol), catalyst (20 mg), 80 °C.
[0107] Subsequently, [Zn-Salen( t Bu)-COF] n+ (Cl - ) n The cycle performance at 80℃, 0.1MPa, and reaction time of 21h is as follows: Fig.12 As shown. [Zn-Salen( t Bu)-COF] n+ (Cl - ) nIt also showed good recycling performance. After 6 cycles, the yield and selectivity of cyclic carbonate were still 97.9% and 99% respectively. Fig.12 a), and after recycling [Zn-Salen( t Bu)-COF] n+ (Cl - ) n The infrared absorption spectrum of the prepared sample is almost unchanged from that of the new sample ( Fig.12 b).
[0108] (3) Substrate adaptability of two-dimensional Zn-Salen catalyst for the addition reaction of CO2 with epoxides
[0109] The catalytic performance of [Zn-Salen( t Bu)-COF] n+ (Cl - ) n The substrate adaptability of [Zn-Salen( t Bu)-COF] n+ (Cl - ) n It shows excellent catalytic activity, and the conversion rate of epoxy compounds and the selectivity of cyclic carbonates both reach 99% (Table 6 Examples 1-4). For glycidol with an electron-donating group (-OH), the yield decreases (Table 6 Example 5), because the electron-donating property of the epoxy compound with an electron-donating group increases the electronegativity of the C atom adjacent to the O atom, increasing the difficulty of nucleophilic attack. The yield of catalytic oxidation of styrene is only 78.6%, which is due to the electron-richness and large steric hindrance of styrene oxide. Disubstituted cyclohexene oxide has two rings and has a large steric hindrance, which limits the nucleophilic attack of anions and greatly reduces the epoxide ring-opening efficiency, so the product yield decreases significantly (Table 6 Example 5), but in all epoxide conversion processes, the selectivity of the corresponding cyclic carbonate products is close to 100%.
[0110] Table 6 [Zn-Salen ( t Bu)-COF] n+ (Cl - ) n Results of catalytic cycloaddition of CO2 with different substrates
[0111]
[0112] Reaction conditions: 80°C, 0.1 MPa, 21 h, substrate 5 mmol, catalyst 20 mg.
[0113] (4) Mechanism of the cycloaddition reaction of CO2 and epoxides catalyzed by Zn-Salen two-dimensional cationic COFs
[0114] like Fig.13 As shown, first, the epoxy compound is activated by the coordination reaction between the oxygen atom and Zn-Salen, and then the balanced anion halogen anion in the cationic COFs nucleophilically attacks the carbon atom with less steric hindrance on the epoxy compound ring to open the ring to form a haloalkoxide intermediate, and the CO2 in the pore undergoes nucleophilic addition with the reaction intermediate after the ring opening and inserts into the Zn-O coordination bond to form a metal-bonded carbonate, and finally, the oxygen atom with strong electronegativity bites back the carbon atom connected to the halogen to form a five-membered ring, and the halogen leaves in the form of negative ion to obtain the final cyclic carbonate. It should be pointed out that for the sake of clarity, this example shows each step of the reaction in the catalytic cycle on different Zn-Salen, and in fact each Zn-Salen center will complete a whole catalytic cycle process.
[0115] In summary, the present invention reacts three-way connected 1,3,5-tri(pyridin-4-yl)benzene with chloromethylated salicylaldehyde compounds to obtain two two-dimensional Zn-Salen cationic bifunctional polymer catalysts. 13 C NMR, XPS, pore size test and thermogravimetric analysis were used to characterize its composition and structure in detail. Physical adsorption tests showed that the two-dimensional Zn-Salen cationic polymer is a mesoporous material. The results of catalytic performance studies showed that the two-dimensional Zn-Salen porous cationic polymer catalyst can achieve high selectivity in the conversion of ECH into the corresponding cyclic carbonate at normal pressure (0.1Mpa). The two-dimensional Zn-Salen cationic polymer containing tert-butyl can almost completely convert ECH into cyclic carbonate within 21 hours at 80°C and 0.1Mpa CO2 pressure. The balanced anion in the two-dimensional Zn-Salen cationic polymer containing tert-butyl is replaced by Br with a stronger nucleophilicity. - and I - Under the same conditions, the reaction time can be significantly shortened, wherein the substitution into I - After that, epichlorohydrin can be 100% converted into cyclic carbonate within 12 hours. In addition, the two-dimensional Zn-Salen porous organic polymer catalyst also has good substrate expansion and cyclic repeatability.
Claims
1. A porous bifunctional catalyst for CO2 cycloaddition reaction, characterized in that: The porous bifunctional catalyst is a two-dimensional cationic porous covalent organic framework, namely Zn-Salen two-dimensional cationic COFs, and its chemical structure is shown in Formula III: Where R is H or t Bu, X is Cl, Br or I.
2. A method for preparing a porous bifunctional catalyst for CO2 cycloaddition reaction according to claim 1, characterized in that: The following steps are involved: (1) Synthesis of quaternary ammonium salt intermediate: chloromethylated salicylaldehyde compound and 1,3,5-tri(pyridin-4-yl)benzene are heated to reflux in acetonitrile for 45-50 hours; after the reaction is completed, the reaction mixture is cooled to room temperature, the yellow precipitate is collected by filtration, and the precipitate is washed alternately with acetonitrile and ether for several times, and vacuum dried to obtain the quaternary ammonium salt intermediate, which is dried and sealed for storage; the molar ratio of the chloromethylated salicylaldehyde compound to 1,3,5-tri(pyridin-4-yl)benzene is (3.5-4.5):1; the ratio of the volume of acetonitrile to the molar amount of the chloromethylated salicylaldehyde compound is (6-7) mL:1 mmol; The structural formula of the chloromethylated salicylaldehyde compound is shown in Formula I: Where R is H or t Bu; The structural formula of the quaternary ammonium salt intermediate is shown in Formula II: Where R is H or t Bu; (2) Synthesis of two-dimensional cationic porous covalent organic frameworks: (2-1) slowly adding a 0.076 mol / L methanol solution of o-phenylenediamine to a 0.025 mol / L methanol solution containing a quaternary ammonium salt intermediate, and stirring at room temperature for 10-14 h to obtain a reaction mixture; the molar ratio of o-phenylenediamine to the quaternary ammonium salt intermediate is 1.5:1; (2-2) zinc chloride is ultrasonically dispersed in methanol to obtain a 0.076 mol / L zinc chloride solution; the molar ratio of zinc chloride to o-phenylenediamine is 1:1; (2-3) Add zinc chloride solution dropwise to the reaction mixture prepared in step (2-1), and a large amount of yellow precipitate appears immediately; then add DMF, continue stirring at room temperature for 5-7 hours, transfer it to a hydrothermal reactor and react at 120-125° C. for 45-50 hours, filter the collected precipitate and extract it with methanol for 22-25 hours, and vacuum dry the remaining solid product to obtain a two-dimensional cationic porous covalent organic framework [Zn-Salen(H)-COF] n+ (Cl - ) n or [Zn-Salen( t Bu)-COF] n+ (Cl - ) n ; (3) [Zn-Salen(H)-COF] n+ (Cl - ) n or [Zn-Salen( t Bu)-COF] n+ (Cl - ) n Place in a saturated KBr or KI aqueous solution and stir thoroughly for 8-12 hours, then centrifuge to separate the solid powder, wash the ion exchange product with deionized water for 3-5 times, and place in an oven to dry to obtain a two-dimensional cationic porous covalent organic framework [Zn-Salen(H)-COF] n+ (Br - ) n or [Zn-Salen(H)-COF] n+ (I - ) n or [Zn-Salen( t Bu)-COF] n+ (Br - ) n or [Zn-Salen( t Bu)-COF] n+ (I - ) n .
3. The method for preparing a porous bifunctional catalyst for CO2 cycloaddition reaction according to claim 2, characterized in that: In step (1), when R is H, the chloromethylated salicylaldehyde compound is 5-chloromethyl-2-hydroxybenzaldehyde, and its preparation process is as follows: Paraformaldehyde (CHO) was added at room temperature n and 2-hydroxybenzaldehyde are added to concentrated hydrochloric acid in a mass ratio of 1:(2.5-3), the mass ratio of concentrated hydrochloric acid to 2-hydroxybenzaldehyde is (2.5-3.0):1, and the paraformaldehyde is completely dissolved by stirring; phosphorus oxychloride is slowly added dropwise to the above reaction mixture using a constant pressure dropping funnel, the mass ratio of phosphorus oxychloride to 2-hydroxybenzaldehyde is 1:(2.8-3.0), and after the dropwise addition is completed, the reaction mixture is vigorously stirred at room temperature for 22-25 hours, and white solid is precipitated during the reaction process; after the reaction is completed, deionized water is added to the reaction mixture, the volume ratio of deionized water to concentrated hydrochloric acid is (1.5-2.0:1), and the solid product is collected by filtration to obtain 5-chloromethyl-2-hydroxybenzaldehyde.
4. The method for preparing a porous bifunctional catalyst for CO2 cycloaddition reaction according to claim 3, characterized in that: The solid product was collected by filtration and washed with a 3% by mass sodium bicarbonate solution and deionized water in sequence until neutral, and then vacuum dried at 55-65° C. for 10-14 h to obtain a crude 5-chloromethyl-2-hydroxybenzaldehyde product; the obtained crude product was recrystallized from petroleum ether 2-3 times to obtain pure 5-chloromethyl-2-hydroxybenzaldehyde.
5. The method for preparing a porous bifunctional catalyst for CO2 cycloaddition reaction according to claim 2, characterized in that: In step (1), when R is t When Bu, the chloromethylated salicylaldehyde compound is 3-tert-butyl-5-chloromethyl-2-hydroxybenzaldehyde, and the preparation process is as follows: 3-tert-butyl-2-hydroxybenzaldehyde, paraformaldehyde and tetrabutylammonium bromide are respectively added to concentrated hydrochloric acid in a mass ratio of 3:(1-1.2):(0.4-0.5), and the mass ratio of concentrated hydrochloric acid to 3-tert-butyl-2-hydroxybenzaldehyde is (1.8-2.0):
1. The reaction mixture is vigorously stirred at room temperature for 60-65h. After the reaction is completed, the reaction mixture is extracted with ether, and the separated organic phase is washed with NaHCO3 solution and NaCl solution in sequence, and then dehydrated with MgSO4, and vacuum dried to obtain a yellow crystalline solid.
6. Use of the porous bifunctional catalyst for CO2 cycloaddition reaction according to claim 1 in the preparation of cyclic carbonates by cycloaddition of carbon dioxide and epoxides.
7. The use according to claim 6, characterized in that: The specific process should be: (1) adding Zn-Salen two-dimensional cationic COFs and epoxide into a reaction kettle and stirring and mixing them thoroughly; the mass ratio of Zn-Salen two-dimensional cationic COFs to epoxide is 1000:(1.5-2.5); (2) The air in the reactor is removed by purging with CO2 3-4 times, and then the reactor is connected to a CO2 cylinder with a constant output pressure. The reactor is then heated to 60-80°C and kept warm for 15-24 hours to obtain a cyclic carbonate.
8. The use according to claim 7, characterized in that: In step (1), the epoxy compound is one of ethylene oxide, propylene oxide, epichlorohydrin, butyl ethylene oxide, styrene oxide and cyclohexene oxide.
Citation Information
Patent Citations
Salen metallic catalyst and preparation method
CN101327452A
Zn-Salen-based ionic polymer catalyst as well as preparation method and application thereof
CN116731271A